Development and application of a low-priced duplex quantitative PCR assay based on SYBR Green I for the simultaneous detection of porcine deltacoronavirus and porcine sapelovirus - Lu, Si-Jia; Ma, Meng-Yao; Yan, Xiao-Guang; Zhao, Fu-Jie; Hu, Wen-Yang; Ding, Qing-Wen; Ren, Hao-Jie; Xiang, Yu-Qiang; Zheng, Lan-Lan (Veterinarni medicina, 2023)
Porcine deltacoronavirus (PDCoV) and porcine sapelovirus (PSV) are two viruses that can cause diarrhoea in pigs and bring great economic loss to the pig industry. In this research, a duplex real-time quantitative polymerase chain reaction (qPCR) assay based on SYBR Green I was developed to simultaneously detect PDCoV and PSV. No specific melting peaks were found in other porcine diarrhoea-associated viruses, indicating that the method developed in this study had good specificity. The detection limits of PDCoV and PSV were 1.0 × 101 copies μl-1 and 1.0 × 102 copies μl-1, respectively. The duplex real-time qPCR assay tested two hundred and three (203) intestinal and faecal samples collected from diarrhoeal and asymptomatic pigs. The positive rates of PDCoV and PSV were 20.2% and 23.2%, respectively. The co-infection rate of PDCoV and PSV was 13.8%. To evaluate the accuracy of the developed method, conventional PCR and singular TaqMan real-time qPCR assays for PDCoV/PSV were also used to detect the samples. The results showed that the duplex real-time qPCR assay was consistent with the singular assays, but its sensitivity was higher than conventional PCR methods. This duplex real-time qPCR assay provides a rapid, sensitive and reliable method in a clinic to simultaneously detect PDCoV and PSV.
Keywords: duplex real-time qPCR; PDCoV; PSV